The Culture Environment Influences Both Gene Regulation and Phenotypic Heterogeneity in Escherichia coli - Smith, Ashley; Kaczmar, Agnieszka; Bamford, Rosemary A.; Smith, Christopher; Frustaci, Simona; Kovacs-Simon, Andrea; O’Neill, Paul; Moore, Karen; Paszkiewicz, Konrad; Titball, Richard W.; Pagliara, Stefano (Frontiers in Microbiology, 2018)
Microorganisms shape the composition of their medium, this in turn having profound consequences on the reprogramming of the population gene expression profile. In this paper we investigate the progressive changes in pH and sugar availability in the medium of a growing Escherichia coli culture. We show how these alterations have a distinct effect on both the cellular heterogeneity within the microbial community, and the gene expression profile of the microbial population. We measure the changes in gene expression profiling as an Escherichia coli population moves from lag, to exponential and finally into stationary phase. We found that ribosomal, TCA cycle, carbon, nitrogen, and amino acid metabolism and transport pathways, linked to the changes in the medium composition, are strongly regulated during the different phases of growth. In order to quantify the corresponding temporal changes in the population heterogeneity, we quantify the fraction of E. coli persisters surviving different antibiotic treatments during the various phases of growth. We show that the composition of the medium in which β-lactams or quinolones, but not aminoglycoside, are dissolved strongly affects the measured phenotypic heterogeneity within the culture. Our findings contribute to a better understanding of the influence of the composition of the culture medium on both the reprogramming in the population gene expression and the emergence of phenotypic variants.